Rekayasa Hukum (Fraus Legis) Dalam Perkawinan Beda Agama: Studi Komparatif Pengakuan Hukum Antara Singapura Dan Indonesia Pasca Sema No 2 Tahun 2023 - Wike Sundari; Sukiati; Iwan (Ameena Journal, 2026)
This study examines the phenomenon of interfaith marriages involving Indonesian citizens (WNI) conducted in Singapore as a response to national legal restrictions following the enactment of Supreme Court Circular Letter (SEMA) No. 2 of 2023. The central issue lies in the conflict between the principle of lex loci celebrationis, which recognizes the formal validity of marriages performed in Singapore, and lex patriae, which requires compliance with material conditions—specifically religious uniformity for Indonesian citizens. Employing a normative juridical method with statutory, comparative, and conceptual approaches, this research aims to analyze the differing roles of religious and civil law in both countries and their legal implications.The findings reveal a fundamental divergence: Indonesia adopts a religious-formalistic system, where religious law constitutes an essential requirement for marital validity, whereas Singapore applies a secular-pragmatic system under the Women’s Charter, separating civil authority from religious doctrine. Marriages conducted by Indonesian citizens in Singapore are considered a form of legal evasion (fraus legis), as they involve an intention to circumvent national law (animus evadendi). SEMA No. 2 of 2023 reinforces the refusal to register such marriages on the grounds of public policy derived from Pancasila values. Consequently, this gives rise to limping marriages, in which couples lack full legal recognition in Indonesia, particularly regarding marital property and inheritance rights. The most significant impact affects children born from such unions, who are legally classified as children born out of wedlock, with limited civil rights and more complex administrative procedures. This study concludes that Indonesia’s current legal policy prioritizes theological legal certainty over the protection of citizens’ civil rights within a global context.